2017
DOI: 10.1136/eb-2017-102719
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based cognitive behavioural therapy for young people with suicide-related behaviour (Reframe-IT): a randomised controlled trial

Abstract: background Suicide-related behaviours are common in young people and associated with a range of negative outcomes. There are few evidencebased interventions; however, cognitive behavioural therapy (CBT) shows promise. Internet delivery of CBT is popular, with potential to increase reach and accessibility. Objective To test the effectiveness of an internet-based CBT program (Reframe-IT) in reducing suicide-related behaviours, depression, anxiety, hopelessness and improving problem solving and cognitive and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 27 publications
1
132
0
Order By: Relevance
“…Our findings further highlight the impact of premature mortality, particularly due to accidental overdose and suicide, among young Australian PWID . Integration of overdose and suicide prevention within youth‐orientated outreach and harm reduction service provision ; including innovation in the use of online and mobile technology , should be further evaluated. Efforts to improve OST coverage and retention; scale up of community naloxone programs, and closer monitoring of mortality risk periods are also indicated .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings further highlight the impact of premature mortality, particularly due to accidental overdose and suicide, among young Australian PWID . Integration of overdose and suicide prevention within youth‐orientated outreach and harm reduction service provision ; including innovation in the use of online and mobile technology , should be further evaluated. Efforts to improve OST coverage and retention; scale up of community naloxone programs, and closer monitoring of mortality risk periods are also indicated .…”
Section: Discussionmentioning
confidence: 99%
“…A trend toward reductions in suicidal behavior was, however, noted by Hetrick et al. (), with no suicide attempts at either 10 weeks or 22 weeks of follow‐up in the intervention group compared to three and two participants attempting suicide in the control group. A fourth study by Franklin et al.…”
Section: Resultsmentioning
confidence: 84%
“…van Spijker et al (2018) reported small treatment effects following online therapy (d = À0.11, 0.15; calculated from marginal means). A trend toward reductions in suicidal behavior was, however, noted by Hetrick et al (2017), with no suicide attempts at either 10 weeks or 22 weeks of follow-up in the intervention group compared to three and two participants attempting suicide in the control group. A fourth study by Franklin et al (2016) also reported fewer participants engaging in suicidal behavior in the active treatment group compared to the control group in two of their studies (study 1: 5 vs. 4 individuals; study 2: 4 vs. 8 individuals; study 3: 3 vs. 5 individuals).…”
Section: Suicide Attemptmentioning
confidence: 84%
“…A randomized controlled trial is underway to study the effectiveness of a safety plan via mobile app in reducing suicidal ideation and behavior versus the traditional safety plan on paper that is used by many institutions before discharging suicidal patients from the emergency room or inpatient psychiatric units (Andreasson et al, ). More research is needed on the effectiveness of Internet‐based cognitive behavioral therapy (CBT) in reducing suicidal behaviors among school students, but early results indicate that young people were engaged and experienced reduced suicidal ideations and other mood symptoms (Hetrick et al, ). Educational websites targeting young people in crisis have demonstrated suicide preventive effects and have been effective in increasing suicide‐related knowledge (Till, Tran, Voracek, & Niederkrotenthaler, ).…”
Section: Prevention and Intervention Opportunitiesmentioning
confidence: 99%